KETERATURAN ANC TERHADAP KEPATUHAN KONSUMSI TABLET BESI SELAMA KEHAMILAAN - Anjelina Puspita Sari; Romlah Romlah (JURNAL KESEHATAN INDRA HUSADA, 2022)
Background: Iron deficiency is still a health problem for pregnant women in Indonesia with a prevalence of 37.1%. This study aims to determine the relationship between ANC regularity and consumption of iron tablets during pregnancy. Methods: This type of research uses observational analytic using a cross sectional design. The sampling technique is tolat sampling, with a total sample of 52 respondents. Data were taken by observing retrospective data from respondents' medical records. The analysis technique uses the Chi-Square test. Results: The statistical test results showed a significant relationship between the regularity of ANC and adherence to iron tablet consumption during pregnancy (pv=0.002). Conclusion: Obedience of pregnant women in consuming iron tablets is very important for monitoring, this monitoring can be done when the mother visits the ANC.